Implementasi Aplikasi Sistem Pendukung Keputusan Kenaikan Jabatan Pegawai Negeri Sipil (Pns) Menggunakan Metode Weight Product Pada Bagian Protokol Dan Dokumentasi Setda Kota Depok - Muhamad Irsan (Faktor Exacta, 2018)
Abstract. One of the main decisions faced is the process of upgrading the civil servant's office of protocol and documentation of setda Depok city. The problem that occurs is the process of determining the objectives, that are not appropriate and there is no effective methods for the process is not in accordance with the target of promotion. To support the results of the methods used are Weighted Product (WP), where each provides factors and alternatives to provide one and the other to provide a rating (ranking). The system generates decisions that will generate more to help better processes.Keywords: Weight Product, Decission Support System.